Measurement Radon Gas Concentration in Selected Soil Samples of The of Al-Nada District in Najaf - Fadel Kadim, Shahad; Najy Hady, Heiyam (International Journal of Engineering and Technology, 2018)
In this study fifty (50) of soil samples of AL-Nada district-Najaf Governorate –Iraq have been collected randomly and studied using  solid state nuclear track detectors (CR-39) to determined 226Ra through counting the number of radon tracks by using CR-39 plastic nuclear track detector ,a long- term measurement technique has been considered using special tube of mean (2.5cm) diameter .The detector was placed at (5cm) height and irradiated for 90 days. The chemical etching performed by using (NaOH) solution of 6.25 normality at etching temperature (70C°)for etching period of (7 hrs  ).Concentration of radon 222Rn has ranged from (171.237±0.0062) Bq/m3 to (31.982±0.0027) Bq/m3with  average value  (99.222±0.2476) Bq/m3 while the specific activityof radon has been ranged from (0.471±1.794) Bq/kg to (0.090±7.682) Bq/kg with average value (0.277 1.320)Bq/kgThe results were found to be comparable or lower than similar global reporting data. Accordingly, this area of soil can be considered to have normal levels of natural background radiation.